# Given f(x) = x^{2 }+ 12x + 26 . Write the quadratic function in vertex form.

**Solution:**

Let y = f(x) = x² + 12x + 26

y = x² + 12x + 26

y - 26 = x² + 12x

y - 26 + 36 = x² + 12x + 36

y + 10 = (x + 6)²

y = (x + 6)² -10

y = (x - (-6))² + (-10)

The __quadratic equation__ is converted into vertex form which is of the form:

y = a(x - h)² + k

a = 1

h = -6 and

k = -10

Hence y = (x - (-6))² + (-10) is the required veryex form.

## Given f(x) = x^{2 }+ 12x + 26 . Write the quadratic function in vertex form.

**Summary:**

Given f(x) = x² + 12x + 26, the quadratic function in vertex form is given as y = (x - (-6))² + (-10)

Math worksheets and

visual curriculum

visual curriculum